Risk factors of postpartum uterine infection and its subsequent effect on fertility of crossbred dairy cows in Bangladesh (International Journal of Natural Sciences, 2016)
Postpartum uterine infection is extremely important in dairy cattle. It is both common and detrimental to reproductive performance. The present study was conducted to investigate the factors responsible for postpartum uterine infection and its subsequent effect on fertility of crossbred dairy cows in Chatmohar Upazila, Pabna District. A total of 317 cows were selected and registered and then follow up them in postpartum period. Reproductive histories and data of the studied cows were assessed by direct interviewing and from record book of the owners and nearby government veterinary hospital. Totally 33 cows were found uterine infected (10.41%) in postpartum period. The case of pyometra was substantially higher in present study in contrast to others. The incidence of uterine infection puerperal metritis, pyometra and endometritis were 1.89%, 5.99% and 2.52% respectively. Dairy cattle calving season and parity reflected greatly on the incidence of uterine infection. Potentially significant (p